Genetic variation in the major mitotic checkpoint genes associated with chromosomal aberrations in healthy humans - Försti, Asta; Frank, Christoph; Smolkova, Bozena; Kazimirova, Alena; Barancokova, Magdalena; Vymetalkova, Veronika; Kroupa, Michal; Naccarati, Alessio; Vodickova, Ludmila; Buchancova, Janka; Dusinska, Maria; Musak, Ludovit; et al. (Cancer letters, 2016)
Non-specific chromosomal aberrations (CAs) are microscopically detected in about 1% of lymphocytes drawn from healthy persons. Causes of CAs in general population are not known but they may be related to risk of cancer. In view of the importance of the mitotic checkpoint machinery on maintaining chromosomal integrity we selected 9 variants in main checkpoint related genes (BUB1B, BUB3, MAD2L1, CENPF, ESPL1/separase, NEK2, PTTG1/securin, ZWILCH and ZWINT) for a genotyping study on samples from healthy individuals (N = 330 to 729) whose lymphocytes had an increased number of CAs compared to persons with a low number of CAs. Genetic variation in individual genes played a minor importance, consistent with the high conservation and selection pressure of the checkpoint system. However, gene pairs were significantly associated with CAs: PTTG1-ZWILCH and PTTG1-ZWINT. MAD2L1 and PTTG1 were the most common partners in any of the two-way interactions. The results suggest that interactions at the level of cohesin (PTTG1) and kinetochore function (ZWINT, ZWILCH and MAD2L1) contribute to the frequency of CAs, suggesting that gene variants at different checkpoint functions appeared to be required for the formation of CAs.
Keywords: Genes, cdc; Spindle checkpoint; Humans; Healthy Volunteers; Lymphocytes; DNA double-stranded break; DNA Breaks, Double-Stranded; lymfocyty; Chromosomal integrity; dvouřetězcové zlomy DNA; Securin; intracelulární signální peptidy a proteiny; Mad2 Proteins; CDC geny; jaderné proteiny; lidé; Cell Cycle Proteins; Mad2 protein; genetická variace; Genetic Variation; Intracellular Signaling Peptides and Proteins; Cytogenetics; chromozomální aberace; M Phase Cell Cycle Checkpoints; Chromosome Aberrations; modely genetické; kontrolní body M fáze buněčného cyklu; Nuclear Proteins; proteiny buněčného cyklu; sekurin; Models, Genetic; zdraví dobrovolníci pro lékařské studie